Effects of Time of Feeding on Psychostimulant Reward, Conditioned Place Preference, Metabolic Hormone Levels, and Nucleus Accumbens Biochemical Measures in Food-Restricted Rats - Zheng, Danielle (2013)
RATIONALE: Chronic food restriction (FR) increases rewarding effects of abused drugs and persistence of a cocaine-conditioned place preference (CPP). When there is a single daily meal, circadian rhythms are correspondingly entrained, and pre- and postprandial periods are accompanied by different circulating levels of metabolic hormones that modulate brain dopamine function. OBJECTIVES: The present study assessed whether rewarding effects of d-amphetamine, cocaine, and persistence of cocaine CPP differ between FR subjects tested in the pre- and postprandial period. MATERIALS AND METHODS: Rats were stereotaxically implanted with intracerebral microinjection cannulae and an electrode in lateral hypothalamus. Rewarding effects of d-amphetamine and cocaine were assessed using electrical self-stimulation in rats tested 1-4 or 18-21 hrs after the daily meal. Non-implanted subjects acquired a cocaine CPP while ad libitum fed, then were switched to FR and tested for CPP at these same times. RESULTS: Rewarding effects of intra-nucleus accumbens (NAc) d-amphetamine, intraventricular cocaine, and persistence of cocaine CPP did not differ between rats tested 18-21 hrs food deprived, when ghrelin and insulin levels were at peak and nadir, respectively, and those tested 1-4 hrs after feeding. Rats that expressed a persistent CPP had elevated levels of p-ERK1, GluA1, and p-Ser845-GluA1 in NAc core, and the latter correlated with CPP expression. CONCLUSIONS: Psychostimulant reward and persistence of CPP in FR rats are unaffected by time of testing relative to the daily meal. Further, NAc biochemical responses previously associated with enhanced drug responsiveness in FR rats are associated with persistent CPP expression.